Analysis of Factors Influencing Work Accidents Among Workers at Exploitation Facilities and Offshore Oil and Gas Production at PT X from 2018 – 2023 - Cahyo Hardo Priyoasmoro; Zulkifli Djunaidi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: The workplace risks faced at PT X oil and gas company, located offshore Natuna, are relatively high evidenced by fluctuations in accidents from 2018 – 2022. In 2018, recordable injury attributable to accidents was recorded, then in 2019-2020, there were no accidents, and the prevalence increased in 2021-2022. The company analyzed the main causes responsible for work accidents during this period and carried out intervention measures in Occupational Health and Safety (OHS) program to reverse the trend in 2023. By implementing OHS program, the number of accidents in recordable injury category fell from 4 (2021- 2022) to 1 (2023). This shows that the program has been successful in managing work accidents. Considering that the investigation and analysis identified unsafe acts as the direct causes, Human Factor Analysis and Classification System (HFACS) method was used to analyze other factors associated with accidents. Objective: This study aimed to investigate OHS program actions at PT X in responding to increased work accidents in 2021-2022, and compare with recommendations for improvements from HFACS method. Method: A qualitative design was used with secondary data, comprising 10 work accidents records and investigation reports for recordable injury cases from 2018 – 2022 available in PT X information system. Subsequently, the secondary data were then classified according to four failure stages in HFACS, namely unsafe acts, the precondition of unsafe acts, unsafe supervision, and organizational influence. This classification produced recommendations for improvement, which were then compared with the prevention intervention program for accidents at PT X. Results: The results showed that OHS program intervention to reduce the number of accidents in 2023 was in accordance with the recommendations of HFACS analysis. Conclusion: The application of HFACS in analyzing accidents records and investigation reports produced relatively comprehensive recommendations by focusing on the component stages. Several additional recommendations from the analysis of latent conditions will further improve OHS performance at PT X.